Marching with Sherman : Through Georgia and the Carolinas with the 154th New York - Dunkelman, Mark H. (Book collections on Project MUSE., 2012)
Marching with Sherman: Through Georgia and the Carolinas with the 154th New York presents an innovative and provocative study of the most notorious campaigns of the Civil War-Union General William Tecumseh Sherman's devastating 1864 "March to the Sea" and the 1865 Carolinas Campaign. The book follows the 154th New York regiment through three states and chronicles 150 years, from the start of the campaigns to their impact today. Mark H. Dunkelman expands on the brief accounts of Sherman's Marches found in regimental histories with an in-depth look at how one northern unit participated in the ca